2002
DOI: 10.1046/j.1471-4159.2002.01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial electron transport chain complex dysfunction in a transgenic mouse model for amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis is a fatal neurodegenerative disease that causes degeneration of motoneurons. Mutation of Cu,Zn superoxide dismutase (SOD1) is one cause for this disease. In mice, expression of mutant protein causes motoneuron degeneration and paralysis resembling the human disease. Morphological change, indicative of mitochondrial damage, occurs at early stages of the disease. To determine whether mitochondrial function changes during the course of disease progression, enzyme activities of mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(122 citation statements)
references
References 65 publications
4
111
0
1
Order By: Relevance
“…Although some of these studies have produced mixed and somewhat contradictory results, the most consistent abnormality in mitochondrial respiratory function has been associated with reduced complex I and IV activity (Browne et al 1998;Kirkinezos et al 2005;Mattiazzi et al 2002;Menzies et al 2002;Rizzardini et al 2006;Son et al 2008). In motor neurons of mutant SOD1 G93A mice a reduction in activity of complex I was observed before disease onset and progressing to inhibition of complex IV at later stages (Jung et al 2002). In neuroblastoma cells overexpressing mutant SOD1 G37R , we observed a decreased activity of complex I in mitochondrial fractions (Coussee et al 2011).…”
Section: Mitochondrial Morphological Abnormalities and Dysfunctions Imentioning
confidence: 62%
See 1 more Smart Citation
“…Although some of these studies have produced mixed and somewhat contradictory results, the most consistent abnormality in mitochondrial respiratory function has been associated with reduced complex I and IV activity (Browne et al 1998;Kirkinezos et al 2005;Mattiazzi et al 2002;Menzies et al 2002;Rizzardini et al 2006;Son et al 2008). In motor neurons of mutant SOD1 G93A mice a reduction in activity of complex I was observed before disease onset and progressing to inhibition of complex IV at later stages (Jung et al 2002). In neuroblastoma cells overexpressing mutant SOD1 G37R , we observed a decreased activity of complex I in mitochondrial fractions (Coussee et al 2011).…”
Section: Mitochondrial Morphological Abnormalities and Dysfunctions Imentioning
confidence: 62%
“…The first evidence of mitochondrial abnormalities came from ultrastructural studies showing aggregates of mitochondria in muscles and spinal cord motor neurons (Sasaki and Iwata 1996) and increased mitochondrial volume in motor nerve terminals of ALS patients (Siklos et al 1996). Consistent with these findings, observations of mitochondrial morphology in cell or animal models of familial ALS showed aggregated, swollen, vacuolated or fragmented mitochondria (Bendotti et al 2001;Coussee et al 2011;Damiano et al 2006;Jaarsma et al 2001;Jung et al 2002;Menzies et al 2002;Raimondi et al 2006;Xu et al 2004).…”
Section: Mitochondrial Morphological Abnormalities and Dysfunctions Imentioning
confidence: 86%
“…Although there is no consensus about the exact role of mitochondrial abnormalities [61], it is accepted that mitochondrial dysfunction is an important hallmark of ALS pathogenesis [5,62,63]. Several authors have shown deficits in mitochondrial function in the spinal cord and muscles of both human patients [64] and animal models of ALS [65][66][67]. Resveratrol improves mitochondrial function and induces biogenesis, although there is some controversy about whether this effect is mediated by AMPK activation [18] or by Sirt1 [16,68].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supporting the MNLS model includes: (1) the concentration of serum lactic acid is higher in persons with ALS (2.77 Ϯ 0.79 mmol/L) and chronic denervated non-ALS patients (2.79 Ϯ 1.29 mmol/L) compared with controls (1.48 Ϯ 0.49 mmol/L) (Siciliano et al, 2001); (2) lactic acid can induce death in neurons (Nedergaard et al, 1991); (3) increased lactate concentrations have been reported in other neurodegenerative conditions such as Huntington disease (Bowling and Beal, 1995) as well as in models of severe and mild brain injury (Ramonet et al, 2004); (4) neuroprotective drugs like nizofenone that block lactate accumulation are used to treat other neurodegenerative diseases ; (5) lactate metabolism in ALS is associated with glutamate excitotoxicity related to neuronal degeneration (Shobha et al, 2007); (6) mitochondrial oxidative phosphorylation is dysfunctional in SOD1 G93A transgenic mice (Jung et al, 2002;Mattiazzi et al, 2002;Vijayvergiya et al, 2005); (7) the malate-aspartate shuttle is inhibited in hSOD1 G93A expressing cells (Mali and Zisapels, 2008) and this may explain the elevated levels of lactate and the damage to neurons (Mali and Zisapels, 2008); (8) hSOD1 G93A -expressing cells showed increased concentrations of cytoplasmic malate dehydrogenase messenger ribonucleic acid (mRNA), malate, and lactate compared with noninduced or wild-type-hSOD1-expressing cells (Mali and Zisapels, 2008); (9) the mitochondrial NADH/NADϩ ratio is elevated in hSOD1 G93A -expressing cells indicating an increased conversion of oxaloacetate to malate in the mitochondria by NADH-dependent mitochondrial malate dehydrogenase MDH (Mali and Zisapels, 2008); (10) impairments in the malate-aspartate shuttle which controls the brain mitochondrial NADH/NAD ϩ balance is known to drive anaerobic metabolism (particularly damaging to neurons) as well as vulnerability to impairments of glycolytic pathways (Mali and Zisapels, 2008); (11) impaired oxidative metabolism and accumulation of lactate was reported in exercising ALS patients (Siciliano et al, 2001);and (12) functional motor unit failure precedes neuromuscular degeneration in motoneuron disease (Balice- Gordon et al, 2000;Fischer et al, 2004).…”
Section: Evidence For the Molecular Modelmentioning
confidence: 99%